Advances in authentication and security protocols for 5G networks: a comprehensive survey - Sunil Kumar Patel; Satya Bhushan Verma; Bineet Kumar Gupta; Shubham Singh; E. Naresh; Piyush Kumar Pareek (Discover Applied Sciences)
Abstract 5G networks, the newest generation of wireless communication in an era of quick technical breakthroughs, promise unmatched speed, dependability, and connection. With this ground-breaking innovation, it is crucial to have strong authentication and security processes to preserve critical data and shield consumers from any dangers. We thoroughly analyze authentication and security mechanisms created expressly for 5G networks in this study. We examine this sophisticated networking paradigm’s numerous difficulties and weaknesses, emphasizing the requirement for rigorous security measures. We also look at encryption algorithms essential for preserving the availability, confidentiality, and integrity of data transferred across 5G networks. Additionally, we go through cutting-edge technologies and standards like network slicing, edge computing, and virtualization that solve the security issues unique to 5G networks. We examine how they could affect authentication and security processes, highlighting both the opportunities and difficulties they present.